Respuestas
Respuesta dada por:
12
4x - 9x + 2 = 7x - 5x - 9
-5x + 2 = 2x - 9
9 + 2 = 2x + 5x
11 = 7x
x =
Listo amigo.......
-5x + 2 = 2x - 9
9 + 2 = 2x + 5x
11 = 7x
x =
Listo amigo.......
Respuesta dada por:
10
▪Enunciado:
![\boxed{4x - 9x + 2 = 7x - 5x - 9} \boxed{4x - 9x + 2 = 7x - 5x - 9}](https://tex.z-dn.net/?f=+%5Cboxed%7B4x+-+9x+%2B+2+%3D+7x+-+5x+-+9%7D)
° Resolvemos reduciendo términos semejantes y despejando la incógnita "x".
![4x - 9x + 2 = 7x - 5x - 9 \\ \\ - 5x + 2 = 2x - 9 \: \: \: \: \: \: \: \: \: \: ( - 1) \\ \\ 5x - 2 = - 2x + 9 \\ \\ 5x + 2x = 9 + 2 \\ \\ 7x = 11 \\ \\ \boxed{ \boxed{x = \frac{11}{7} }} 4x - 9x + 2 = 7x - 5x - 9 \\ \\ - 5x + 2 = 2x - 9 \: \: \: \: \: \: \: \: \: \: ( - 1) \\ \\ 5x - 2 = - 2x + 9 \\ \\ 5x + 2x = 9 + 2 \\ \\ 7x = 11 \\ \\ \boxed{ \boxed{x = \frac{11}{7} }}](https://tex.z-dn.net/?f=4x+-+9x+%2B+2+%3D+7x+-+5x+-+9+%5C%5C++%5C%5C++-+5x+%2B+2+%3D+2x+-+9+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+%28+-+1%29+%5C%5C++%5C%5C+5x+-+2+%3D++-+2x+%2B+9+%5C%5C++%5C%5C+5x+%2B+2x+%3D+9+%2B+2+%5C%5C++%5C%5C+7x+%3D+11+%5C%5C++%5C%5C++%5Cboxed%7B+%5Cboxed%7Bx+%3D++%5Cfrac%7B11%7D%7B7%7D+%7D%7D)
° Resolvemos reduciendo términos semejantes y despejando la incógnita "x".
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años